Influence of Derivatization Temperature and Butylated Hydroxytoluene on the Content of Malondialdehyde in Liver Homogenates - Konev, A.D.; Aksenov, I.V.; Tutelyan, V.A. (Biomedical Chemistry: Research and Methods, 2024)
Malondialdehyde (MDA) is a product of lipid peroxidation that is widely used as a marker of oxidative stress in biomedical research. Detectable levels of MDA can vary significantly, which may be due to its formation in vitro during sample preparation. The purpose of the work was to analyze the methodological reasons for overestimating the malondialdehyde content in the liver and to find approaches to eliminate the flaws of the method. The amount of MDA was estimated by its derivatization with 2-thiobarbituric acid (TBA) with subsequent analysis by HPLC with fluorimetric detection. Increasing the derivatization temperature had no significant effect on the intensity of MDA-TBA complex formation when standard MDA solutions were used, but led to a sharp increase in its content in liver homogenates, which was dose-dependently prevented by the inclusion of butylhydroxytoluene (BHT) in the reaction mixture. The results obtained may be in demand for the development of methods for the analysis of MDA in organs and tissues, as well as for the interpretation of relevant data from biomedical studies.